2023
DOI: 10.20944/preprints202301.0470.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Molecular Hydrogen in the Pathophysiology and Management of Cardiovascular and Metabolic Diseases

Abstract: There is evidence that behavioral risk factors such as western type diet, and life style can predispose to oxidative stress, deficiency in antioxidant status, hyperglycemia, dyslipidemia and increase in inflammation in tissues of various organs: beta cells of the pancreas, LDL receptors in the hepatocytes, endothelium, neurons, osteocytes and gut. Further studies indicate that diets rich in antioxidant flavonoids, omega-3 fatty acids and fiber in foods were inversely associated whereas western-type foods were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Increasing hydrogen (H 2 ) intake is one such strategy, offering significant antioxidative and anti-inflammatory properties, which may provide an advantage in fatigue alleviation [11,12]. Recent studies have suggested that taking in H 2 in the form of gas and water (i.e., hydrogen-rich water, HRW) can help alleviate the symptoms (e.g., dyspnea) of COVID-19 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing hydrogen (H 2 ) intake is one such strategy, offering significant antioxidative and anti-inflammatory properties, which may provide an advantage in fatigue alleviation [11,12]. Recent studies have suggested that taking in H 2 in the form of gas and water (i.e., hydrogen-rich water, HRW) can help alleviate the symptoms (e.g., dyspnea) of COVID-19 [13,14].…”
Section: Introductionmentioning
confidence: 99%